Implementasi Sistem Manajemen Mutu ISO 9001:2015 Pada Proyek Pembangunan Gedung Ciputra School of Business Makassar - Donatus Lasa; Josefine Ernestine Latupeirissa; Lasty Dinulfy R.KS (Program Studi Teknik Sipil UKI Paulus-Makassar, 2022)
The implementation of a quality management system based on ISO 9001: 2015 in construction services at this time is a very appropriate momentum because it can provide added value for companies that apply. Basically, the purpose of this research aims to conduct a study and find out the benefits obtained from the implementation of a quality management system based on ISO 9001:2015 on the Ciputra school of business Makassar development project. There is also a method used is the Qualitative Descriptive method which is expected to be able to provide a systematic and factual description and description of the facts, nature, and relationships of phenomena studied in this project. As for some of the clauses contained in IS0 9001:2015, which are references in this research, namely (1) Scope, (2) Normative reference, (3) Terms and Definition, (4) Organizational context, (5) Leadership, (6) Planning, (7) Support, (8) Operational, (9) Work evaluation and (10) Improvement. Based on the data obtained from this study, there are 15 respondents who are based on the results of direct observations and strengthened by the data obtained such as quality control and material testing. The results of this study show that PT. Nusa Konstruksi Enjiniring has implemented the clauses contained in ISO 9001:2015 as evidenced by quality control of the materials used.